Exploring Educational Values in Pekalen Rafting Tourism as a Social Studies Learning Resource on Environmental Diversity at MTs Negeri 9 Jember - Aini, Kuratul (IJIE International Journal of Islamic Education, 2024)
This research is motivated by the importance of real experience in learning to improve students' understanding of teaching materials, especially in environment-based contextual learning. This study aims to identify educational values in Pekalen Rafting Tour to be used as a learning resource in social studies subjects, especially the theme of environmental diversity. The research method used is a qualitative approach with observation, interview, and literature study techniques. The research subjects consisted of Pakelan Rafting in Probolinggo district tourist sites and students of class VII D MTs Negeri 9 Jember. The results showed that Pekalen Rafting Tourism has potential educational values that can be applied to several subthemes of social studies learning, such as location of residence, climate change, potential natural disasters, as well as economic activities and social interactions. This tour not only offers rafting activities, but also a means to learn about social, cultural, ecological and local economic values. This tourism activity has a positive impact, both in increasing students' awareness of the importance of environmental conservation and in understanding the interaction of local communities with tourists. This study concludes that the integration of values from Pekalen Rafting Tour in social studies learning is able to enrich students learning experience especially by students of MTs Negeri 9 Jember and provide relevant real-life examples to support their understanding of environmental diversity material.